2001
DOI: 10.1021/ol010193a
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Palladium(II)-Mediated Alkoxy Carbonylation as a Route to Functionalized Tetrahydropyrans. Synthesis of the C9−C32 Segment of Phorboxazole A

Abstract: [reaction: see text] Hydroxy alkene 12, synthesized stereoselectively from 2-methyloxazole-4-carboxaldehyde, underwent intramolecular methoxy carbonylation in the presence of palladium(II) acetate to give 13 in which all five stereogenic centers around the tetrahydropyran correspond to those in ring C of phorboxazole A. Aldehyde 15, derived from 13, was linked to hydroxy alkene 23 via a Wittig coupling, and the composite 25 was subjected to a second palladium(II) acetate mediated methoxy carbonylation to yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…White has also used a palladium( II ) catalysed cyclisation in his construction of the C‐ring of phorboxazole A. After much experimentation he found that the optimal conditions were to use Pd(OAc) 2 in a MeOH/MeCN solvent mix, which furnished a 70 % yield of the C‐ring THP 59 (Scheme ) 43. A similar strategy has also been employed by Kitching in his synthesis of one of the THP rings in the bistramide series of marine metabolites 44…”
Section: Cyclisation Onto Unactivated Carbon–carbon Double Bondsmentioning
confidence: 99%
“…White has also used a palladium( II ) catalysed cyclisation in his construction of the C‐ring of phorboxazole A. After much experimentation he found that the optimal conditions were to use Pd(OAc) 2 in a MeOH/MeCN solvent mix, which furnished a 70 % yield of the C‐ring THP 59 (Scheme ) 43. A similar strategy has also been employed by Kitching in his synthesis of one of the THP rings in the bistramide series of marine metabolites 44…”
Section: Cyclisation Onto Unactivated Carbon–carbon Double Bondsmentioning
confidence: 99%
“…18 Although the method has been demonstrated in the context of tetrahydrofuran synthesis, 19 its application to the construction of tetrahydropyrans has received relatively little attention. 20 In the present case, the outcome leading from a hex-1-en-6-ol to the pentasubstituted tetrahydropyran of 4 was known 21 but many features of the reaction, including its mechanism, were obscure. Two observations were noted in a previous exercise that portended problems for the present study.…”
Section: Synthesis Of the C20-c32 Subunitmentioning
confidence: 72%
“…A palladium-mediated hydroxy-palladation-carbonylation sequence was used in the synthesis of a segment of phorboxazole A [137] The palladium-catalyzed sequential carbonylative esterification was used in the synthesis of macrosphelide A [138] (Scheme 120).…”
Section: Hydroxy-palladation-carbonylationmentioning
confidence: 99%